Ecosociocentrism: The Earth First Paradigm for Environmental Sustainability and Sustainable Development - Upreti, Gopi (Nepal Journal of Science and Technology, 2021)
Environmental destruction and degradation that have occurred on planet Earth can be attributed largely to the current neo-liberal economic development paradigm, that considers Nature as simply the resource to be extracted and processed for human consumption and material growth. This paradigm does not consider the intrinsic values in Nature, including the values of life support-services, and goods of the natural ecosystem in the economic valuation system, and therefore, maintaining a healthy, productive, and resilient natural ecosystem becomes simply outside its analytical framework. The most important question that needs to be embedded into any development model is the question of values. If the assumptions of the current economic development model are not restructured and the ecological facts and values are not integrated into economic development model, humanity will inevitably face existential crisis on planet Earth. The scientific epistemology that embodies ecological principle of diversity, ecosystem resilience, interconnectedness, self-organizing complexity, and life sustaining environmental services provides the basis for building social and environmental sustainability. This necessitates the need for the integration of environmental ethics into development framework that can provide the guiding principle for human behavioral conduct. It is argued here that there is a need for a pragmatic environmental ethical paradigm that can integrate both the instrumental and intrinsic values in Nature and promote sustainable development that can lay the foundation for eco-civilization. Recognizing our fundamental interconnectedness with other life forms, self-organizing complexity of the living system and the interdependent nature of our existence, it behooves that development be pursued with a pragmatic environmental ethics that recognizes both the instrumental and intrinsic values in sociosphere (society) and ecosphere (nature). Ecosociocentrism, the proposed ethical framework, recognizes instrumental and intrinsic values in ecosphere and sociosphere. Ecosociocentrism envisages to integrate these values prevalent in ecosphere and sociosphere. Ecosociocentrism claims to provide a pragmatic environmental and development ethical framework for human behavioral conduct to live sustainably in good stewardship with Planet Earth, thus, paving the way to a new era of ecocivilization.